Dinamika Spasial dan Temporal Struktur Komunitas Zooplankton di Teluk Jakarta - Masykhur Abdul Kadir; Ario Damar; Majariana Krisanti (Jurnal Ilmu Pertanian Indonesia, 2015)
Study of spatial and temporal dynamics of zooplankton community structure in the Jakarta Bay. The purpose are analyzing the abundance, distribution, diversity, and dominance index with indicators of water quality spatial and temporal waters of Jakarta Bay. The research was conducted from July-October 2013. Sampling was done four times (July, August, September, and October). The water quality was analysed by Laboratory Productivity and Water Environment at Department of Resources Management, Faculty of Fisheries and Marine Sciences, Bogor Agricultural University. Zooplankton were analyzed using the method of enumeration (census SRC), in Micro Biology Laboratory Faculty. Based on the distribution patterns were its indicates that the landward dissolved oxygen (DO) is increasingly high, especially in August, September, and October, and increase the abundance of zooplankton as much as 1.3106 Ind/m3. DO with a high spatial concentration value reaches the range of 6.2-14.5 mg/L in Muara Marunda (Station 10), and increase the abundance of zooplankton as much as 5.1106 Ind/m3, with a majority composition of crustacea. Results of classification was diversity moderate, stable uniformity, and high dominance index.